Acute and chronic impacts of heat stress on planetary health - Sampath, Vanitha; Shalakhti, Omar; Veidis, Erika; Efobi, Jo Ann Ifeoma; Shamji, Mohamed H.; Agache, Ioana; Skevaki, Chrysanthi; Renz, Harald; Nadeau, Kari C. (Allergy (Copenhagen), 2023)
Heat waves are increasing in intensity, frequency, and duration causing significant heat stress in all living organisms. Heat stress has multiple negative effects on plants affecting photosynthesis, respiration, growth, development, and reproduction. It also impacts animals leading to physiological and behavioral alterations, such as reduced caloric intake, increased water intake, and decreased reproduction and growth. In humans, epidemiological studies have shown that heat waves are associated with increased morbidity and mortality. There are many biological effects of heat stress (structural changes, enzyme function disruption, damage through reactive oxygen or nitrogen species). While plants and animals can mitigate some of these effects through adaptive mechanisms such as the generation of heat shock proteins, antioxidants, stress granules, and others, these mechanisms may likely be inadequate with further global warming. This review summarizes the effects of heat stress on plants and animals and the adaptative mechanisms that have evolved to counteract this stress.